Fostering Pre-service Physical Educators’ Retention of Concepts in a Professional Education Course Using Moneypoly Game - Almario, John Ivan F.; Castro, Rafael Luis G.; Pabustan, Carl Jemuel S.; David, Christian Jay P.; Macabali, Allen J.; Tolentino, Julius Ceazar G.; Valenzuela, Luwy R. (Future Science / FSH-PH Publications, 2023)
Diversified development of educational strategies has been increasingly growing in the field of teacher education to address the challenges in residential-based learning brought by the virtual classroom setting. Necessarily, the application of game-based learning (GBL) is viewed to significantly contribute to complementing the students' learning deficiencies. Hence, this study was conducted to increase concept retention among pre-service physical educators (PSPEs) through a game-based assessment strategy called moneypoly game. This descriptive-qualitative collaborative action research study comprised 48 student-participants enrolled in the professional education course, “Curriculum and Assessment in Physical Education and Health Education for K to 12”, at a teacher education institution in Central Luzon, Philippines during the first semester of the academic year 2022-2023. Educational activities related to the moneypoly game were implemented multiple times during the face-to-face class sessions. Subsequently, open-ended reflective questionnaires were administered to obtain authentic and valid data to capture the increment of concept retention among the PSPEs. Adhering to Braun and Clarke’s Thematic Analysis technique, students’ responses were themed via qualitative analysis software powered by MAXQDA Analytics Pro 2022. Findings revealed three (3) emerging themes that helped learners retain long-term memory of the lessons' concepts. This includes (1) learners’ experiences in the moneypoly game that strengthen their concept retention, (2) contributing factors to students’ constant participation, and (3) significant recommendations to improve the game-based assessment strategy in the next cycle. These characteristics of the moneypoly game influenced the way that students learned and remembered information. This led to the perception that the intervention generated multiform driving forces for the learners' all-encompassing learning. The exploration and utilization of GBL could be applied to other areas of discipline to corroborate the findings made in this study.